OPTIMIZATION OF FUNCTIONAL LOAD DURING ORTHOPEDIC TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The paper discusses the features of choosing the functional loading mode during the prosthetic stage of dental implantation. One-stage and two-stage implantation methods are compared. A single-stage implantation shortens treatment time and allows for rapid functional restoration, but increases the risk of implant micromovements and peri-implantitis due to early loading. The two-stage technique, on the contrary, ensures more stable osseointegration and reduces inflammatory complications, but requires a longer treatment period. Special attention is paid to the role of stomatoscopy in monitoring the condition of peri-implant tissue and early detection of inflammation. The study emphasizes the importance of an individualized approach in selecting the implantation method and loading protocol to improve treatment outcomes.